#45 Evaluation of anthelmintic activity of hydroalcoholic extracts of Acalypha indica leaves and its phytochemical analysis using Fourier Transform Infrared - M, John Staines; K, Gladys Kalpana; E, Rajesh Kumar; P, Maheswaran (Journal of Pharmaceutical Chemistry, 2022)
Helminthiasis, also known as worm infection, is any macroparasitic disease of humans and other animals in which a part of the body is infected with parasitic worms, known as helminths. There are numerous species of these parasites, which are broadly classified into tapeworms, flukes, and roundworms. Acalypha indica is a medicinal plant that is widely used in traditional medicine to treat many diseases like insect bites, infections, sore throat, ulcers, etc. The aim of this study is to evaluate the anthelmintic activity of hydroalcoholic extracts of Acalypha indica leaves and its phytochemical analysis using Fourier transform infrared. Phytochemical constituents of hydroalcoholic extracts of Acalypha indica leaves were analyzed using Fourier transform infrared (FTIR). 50 mL of a formulation containing different concentrations of crude aqueous extract (10, 25, 50, and 100 mg/mL in distilled water) were prepared and 6 worms of the same type were placed in it and the anthelmintic activity of hydroalcoholic extracts of Acalypha indica leaves against earthworm Pheretima posthuma was evaluated. As a result of FTIR analysis, the hydroalcoholic extracts of Acalypha indica leaves showed the presence of coumarin, flavonoids, tannin, phenolic compound, saponin, quinone, and alkaloids. In investigating the anthelmintic action of formulation against adult Indian earthworms, the values of paralytic time and death time of formulation were less when compared to the positive control Albendazole. The ethanolic extract at dose 40 mg/mL caused paralysis in 12 min and death in 110 min against Pheretima posthuma compared to the reference standard Albendazole (10 mg/mL) showed the same at paralysis time 28 min and death time 130 min. The ethanolic extract of Acalypha indica leaves exhibits anthelmintic activity in dose-dependent manner. The ethanolic extract showed significant anthelmintic activity when compared to the reference drug Albendazole. The present work concludes that the hydroalcoholic extracts of Acalypha indica leaves can act as a more suitable herbal treatment against helminths infection and further effectively formulate as an effective dosage form.
Keywords: aaa